Evaluation of ultrasound scanning as a method for measuring subcutaneous fat in Svalbard reindeer - Stien, Audun; Irvine, R. Justin; Langvatn, Rolf; Ropstad, Erik (Rangifer, 2003)
The fitness of an animal is generally strongly dependent on its body condition. A reliable measure of body condition is therefore valuable in ecological studies.